El espacio insular: ¿utopía queer en un mundo straight? Análisis de Minificción para niñxs LGTBI de Sayak Valencia - Palaisi, Marie-Agnès (Moderna Språk, 2024)
LGBTQI+ populations have often been relegated to (gay) ghettos where the biopolitics of nation-states can more easily control so-called "dissident" subjects. Some queer people resist hegemonic mandates from a strategy of deterritorialization and reappropriation of spaces of exclusion and ostracism in order to empower themselves following the positions occupied by Donna Haraway and Paul B. Preciado. Latin American queer literature harbours several heterotopias: there are brothels, asylums and prisons where dissident subjects resignify themselves and rewrite the history of nations from the margins. Some writers, such as Sayak Valencia (Mexico, 1980), even turn these out-of-the-ordinary territories into utopian places where new societies can be invented. In Minificción para niñxs LGTBI, she imagines the construction of a loving relationship between Amarillo and Rayas, reformulating non-binary identities on the island they inhabit. In this remote space, protected from attempts at assimilation, she creates the conditions for a different kind of narrative of self. To analyse this text, I will rely on the thought of Esteban Muñoz in Utopía queer, a fundamental text for thinking about the “queerness” to come.